Mendukung Upaya Perlindungan Penyu Belimbimg (Dermochelys coriacea) Melalui Pendidikan (Program KKN Wau-Weyaf, Abun): Supporting efforts of the Leatherback Turtle (Dermochelys coriacea) through Education Approach (Wau-Weyaf, Abun KKN Program) - Freddy Pattiselanno; Natanael Natumnea; Kuswanto Kuswanto; Muhamad Ansarudin; Yosefina M. Goban; Evi S.H. Kararbo; Martha Kayadoe; Eli F. Karubaba (IGKOJEI: Jurnal Pengabdian Masyarakat, 2021)
ABSTRACT Wau-Weyaf Beach is the nesting ground of six species of turtles, including the world's largest turtle, the leatherback turtle (Dermochelys coriacea). The University of Papua (UNIPA) Manokwari, since 2009 has been directly involved in the turtle nesting area protection program by involving the students of UNIPA through the Community Service Program (KKN). In 2016, students carried out the KKN Program starting from June 30th to August 16th in Kampung Wau-Weyaf, one of the leatherback turtles’ egg-laying locations in Abun. This paper is a part of the Community Service Program which is carried out in the said village. The activities conducted during the KKN include both formal and non-formal education, religious education, and environmental education. Education-based KKN directly helps to improve public awareness which, in turn, supports the efforts to protect and save the leatherback turtles (Dermochelys coriacea) on the coast of Abun, Tambrau. The same approach is also able to improve the calistung (the capability to read, write, and count) ability of school children along with their awareness to maintain the cleanliness of their homes, school, and village environment. Keywords: Education; Conservation; Turtle; Wau-Weyaf ABSTRAK Pantai Wau-Weyaf merupakan tempat bertelur bagi 6 jenis penyu, termasuk penyu terbesar di dunia, Penyu Belimbing (Dermochelys coriacea). Universitas Papua (UNIPA) Manokwari, sejak tahun 2009 telah terlibat secara langsung dalam program perlindungan kawasan peneluran penyu ini melalui pelibatan mahasiswa melalui program Kuliah Kerja Nyata (KKN). Pada tahun 2016, mahasiswa Universitas Papua (UNIPA) melaksanakan program KKN yang dilaksanakan antara tanggal 30 Juni sampai dengan 16 Agustus 2016 di Kampung Wau-Weyaf. Tulisan ini merupakan bagian dari pelaksanaan kegiatan KKN yang dilaksanakan di kampung Wau-Weyaf sebagai salah satu lokasi peneluran telur penyu belimbing di Abun. Kegiatan yang dilakukan meliputi pendidikan formal dan non-formal, pendidikan agama, dan pendidikan lingkungan. KKN berbasis pendidikan yang dilakukan secara langsung membantu meningkatkan penyadar tahuan masyarakat yang menunjang usaha perlindungan dan penyelamatan penyu belimbing (Dermochelys coriacea) di pesisir Abun, Tambrau. Pendekatan yang sama juga mampu meningkatkan kemampuan calistung anak-anak sekolah dan kesadaran menjaga kebersihan lingkungan rumah, sekolah dan kampung. Kata kunci: Pendidikan; Konservasi; Penyu; Wau-Weyaf